KEBIJAKAN PENATAAN TENAGA HONORER DI LINGKUNGAN INSTANSI SEKRETARIAT DAERAH KABUPATEN PELALAWAN TAHUN 2022 - Halomoan, Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research explores the decision of the Regional Secretariat of Pelalawan Regency to increase the number of honorary staff and has not yet eliminated the honorary staff causing problems with staffing and inequality in the implementation of PP Number 49 of 2018 regarding the implementation of Law No. 5 of 2014 concerning ASN and the elimination of honorary staff in the environment. government agencies. There are additional honorary staff filling the fields at the Regional Secretariat of Pelalawan Regency every year. Increasing the number of honorary staff within the Pelalawan Regional Secretariat is contrary to Government Regulation no. 49 of 2018 and the Pelalawan regional government should receive sanctions according to the contents of the PP where the regional government is prohibited from adding honorary staff to its work environment. The results of the research show that the position of Honorary Staff in the Regional Secretariat of Pelalawan Regency after the enactment of Law Number 5 of 2014 concerning State Civil Apparatus has disappeared. Because the issuance of the ASN Law was to reform the ASN management system based on a merit system. In contrast to the old Civil Service Law, the ASN Law only regulates civil servants. The ASN Law divides ASN into two types, namely: PNS and PPPK. The ASN Law which replaced the Basic Civil Service Law no longer allows the appointment of non-permanent employees. This results in the loss of the position of honorary staff as an element of the state apparatus. This research concludes that honorary staff are an important component in the performance of the Regional Secretariat of Pelalawan Regency, which fills the void of human resources in the Regional Secretariat of Pelalawan Regency, and the dependence on honorary staff of the Regional Secretariat of Pelalawan Regency causes a negative impact if the honorary staff are eliminated referring to central government regulations regarding prohibitions on the appointment of honorary staff. Keywords: Policies, Structuring, Honorary Staff